Exploring the utilization of a differentiated assessment tool among primary school teachers in Sabah, Malaysia - Majuddin, Christye (2022)
The 21st century classrooms have seen a broadening spectrum of students’ diversity. To address the individual learning needs of the students, differentiated assessment is deemed as one of the best approaches since it informs differentiated instruction, and vice versa. Besides that, the implementation of the current school-based assessment (SBA) advocates personalized learning and the use of alternative assessment to curb the longstanding practice of the traditional way of assessing students. There are substantial number of studies that managed to highlight the importance of addressing students’ diverse needs through the practice of differentiated assessment and the utilization of assessment tools that support differentiation. However, these studies did not emphasize on the principles of differentiated assessment when discussing on the tools used. Therefore, this study aimed to explore the utilization of a differentiated assessment tool named PutraPacer among primary school teachers in Sabah. Framed by the Activity Theory, this study employed a qualitative research design with five primary school teachers as participants. The data were collected through observation, interviews, and document analysis and further analysis were carried out using Creswell’s data analysis spiral and Saldaña’s two-cycle coding methods. The findings that emerged suggest that the utilization of PutraPacer (i) promotes students to demonstrate their learning progress, (ii) allows students to engage in active learning, (iii) supports successful instructional planning, (iv) functions as a platform for personalized learning, (v) is convenient and time saving, (vi) fosters self-paced learning, (vii) catalyzes Education 4.0. In general, the findings revealed that the use of a differentiated assessment tool could address students’ diverse needs in learning. The use of a differentiated assessment tool is also relevant in today’s classroom since education now is moving towards digitalization, in line with the demand of the Fourth Industrial Revolution.